2022
DOI: 10.3390/bioengineering9100565
|View full text |Cite
|
Sign up to set email alerts
|

RTF-RCNN: An Architecture for Real-Time Tomato Plant Leaf Diseases Detection in Video Streaming Using Faster-RCNN

Abstract: In today’s era, vegetables are considered a very important part of many foods. Even though every individual can harvest their vegetables in the home kitchen garden, in vegetable crops, Tomatoes are the most popular and can be used normally in every kind of food item. Tomato plants get affected by various diseases during their growing season, like many other crops. Normally, in tomato plants, 40–60% may be damaged due to leaf diseases in the field if the cultivators do not focus on control measures. In tomato p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Faster R-CNN and YOLOv3 algorithms are generally improved according to the actual requirements. The improved Faster R-CNN tends to improve detection accuracy ( Alruwaili et al, 2022 ; Nawaz et al, 2022 ), and the improved YOLOv3 algorithm emphasizes the improvement of detection speed ( Liu and Wang, 2020 ; Tian et al, 2019 ). Hence, balancing and optimizing detection accuracy and detection speed plays a major role in plant disease identification.…”
Section: Discussionmentioning
confidence: 99%
“…Faster R-CNN and YOLOv3 algorithms are generally improved according to the actual requirements. The improved Faster R-CNN tends to improve detection accuracy ( Alruwaili et al, 2022 ; Nawaz et al, 2022 ), and the improved YOLOv3 algorithm emphasizes the improvement of detection speed ( Liu and Wang, 2020 ; Tian et al, 2019 ). Hence, balancing and optimizing detection accuracy and detection speed plays a major role in plant disease identification.…”
Section: Discussionmentioning
confidence: 99%
“…Velumani et al [16] used Faster R-CNN to study plant density in the early stages and concluded that the super-resolution method showed significant improvement. Alruwaili et al [17] used fast R-CNN to study tomatoes, and the final results showed that the accuracy of the RTF-RCNN proposed in the study was as high as 97.42%, which is better than traditional methods. The most common research direction is using different methods to identify different crops and ultimately obtain relatively suitable methods for identifying various crops [18][19][20].…”
Section: Introductionmentioning
confidence: 88%
“… Seetharaman and Mahendran (2022) proposed using a convolutional recurrent neural network for banana leaf disease detection. Alruwaili et al. (2022) proposed real-time faster region convolutional neural network (RTF-RCNN) for the real-time detection of tomato leaf diseases in video streams.…”
Section: Related Workmentioning
confidence: 99%